The book of blood and shadow [compact disc, unabridged] - Wasserman, Robin (Listening Library, 2012)
While working on a project translating letters from sixteenth-century Prague, high school senior Nora Kane discovers her best friend murdered with her boyfriend the apparent killer and is caught up in a dangerous web of secret societies and shadowy conspirators.